SHOCKED ROCKS AND IMPACT GLASSES FROM THE EL'GYGYTGYN IMPACT STRUCTURE, RUSSIA - Gurov E.P.; Koeberl C. (My University, 2004)
The El'gygytgyn impact structure is about 18 km in diameter and is located in the central part of Chukotka, arctic Russia. The crater was formed in volcanic rock strata of Cretaceous age, which include lava and tuffs of rhyolites, dacites, and andesites. A mid-Pliocene age of the crater was previously determined by fission track (3.45 ± 0.15 Ma) and 40Ar/39Ar dating (3.58 ± 0.04 Ma). The ejecta layer around the crater is completely eroded. Shock-metamorphosed volcanic rocks, impact melt rocks, and bomb-shaped impact glasses occur in lacustrine terraces but have been redeposited after the impact event. Clasts of volcanic rocks, which range in composition from rhyolite to dacite, represent all stages of shock metamorphism, including selective melting and formation of homogeneous impact melt. Four stages of shocked volcanic rocks were identified: stage I (≤35 GPa; lava and tuff contain weakly to strongly shocked quartz and feldspar clasts with abundant PFs and PDFs; coesite and stishovite occur as well), stage II (35–45 GPa; quartz and feldspar are converted to diaplectic glass; coesite but no stishovite), stage III (45–55 GPa; partly melted volcanic rocks; common diaplectic quartz glass; feldspar is melted), and stage IV (>55 GPa; melt rocks and glasses). Two main types of impact melt rocks occur in the crater: 1) impact melt rocks and impact melt breccias (containing abundant fragments of shocked volcanic rocks) that were probably derived from (now eroded) impact melt flows on the crater walls, and 2) aerodynamically shaped impact melt glass “bombs” composed of homogeneous glass. The composition of the glasses is almost identical to that of rhyolites from the uppermost part of the target. Cobalt, Ni, and Ir abundances in the impact glasses and melt rocks are not or only slightly enriched compared to the volcanic target rocks; only the Cr abundances show a distinct enrichment, which points toward an achondritic projectile. However, the present data do not allow one to unambiguously identify a meteoritic component in the El'gygytgyn impact melt rocks.
Keywords: El’gygytgyn impact structure; Chukotka